Jovita Fuentes, dakilang tinig ng dakilang awit - Chung, Lilia Hernandez (Quezon City : Foundation for Nationalist Studies, 1995)
Biography of Jovita Fuentes, b. 1895, a Filipina national artist.
In Tagalog.
Keywords: Fuentes, Jovita, -- 1895-; Sopranos (Singers) -- Philippines -- Biography